Platinum-assisted post deposition annealing of the n-Ge/Y2O3 interface. (13th June 2016) - Zimmermann, C; Bethge, O; Lutzer, B; Bertagnolli, E
Abstract: The impact of annealing temperature and annealing duration on the interface properties of n-Ge/Y2 O3 /Pt MOS-capacitors is investigated employing an ultrathin catalytically acting Pt-layer. X-ray photoelectron spectroscopy analysis has been used to verify an enhanced growth of GeO2 and thermally stabilizing yttrium germanate at the n-Ge/Y2 O3 interface induced by an oxygen post deposition annealing (PDA). Especially at 500 °C and 550 °C high quality Ge/Y2 O3 interfaces have been achieved resulting in very low interface trap density of 7.41*10 10 eV −1 cm −2 . It is shown that either a short oxygen annealing at higher temperatures (550 °C) or a long time annealing at lower temperatures (450 °C) are appropriate to realize low interface trap density ( D it ). It turns out that a Pt-assisted PDA in combination with a final PMA are needed to reduce hysteresis width significantly and to bring flat band voltages toward ideal values.